ANALYSIS OF TRANSIENT OVERVOLTAGES DUE TO LIGHTNING SURGES AT 150KV MAKALE TANA TORAJA SUBSTATION - Bayu Lopari, Argia; Zulhajji, Zulhajji; Tjandi, Yunus (Jurnal Media Elektrik, 2025)
Transient overvoltage is a phenomenon in the power system that can be caused by lightning or switching surges. These overvoltages have large amplitudes and short durations, potentially damaging equipment, especially the Circuit Breaker, leading to failure in power distribution. As such, analyzing transient overvoltage is critical for understanding its impact and for designing systems that can withstand such surges. This study investigates transient overvoltages at PT PLN (Persero) 150 kV Makale Tana Toraja Substation, calculating the highest possible transient overvoltage that could affect Circuit Breakers. The research employs a quantitative descriptive approach with an Ex-Post Facto design, using the lattice diagram method to analyze the transient overvoltage behavior. Findings reveal that the highest recorded transient overvoltage was 227.231 kV, with values decreasing as the distance from the lightning strike increases. Furthermore, calculations suggest that in the case of properly functioning arresters, transient overvoltage values at Circuit Breakers 1 and 2 are 512.33 kV and 542.514 kV, respectively. However, if the arresters are damaged, these values increase significantly to 1031.94 kV and 1028.814 kV. This study emphasizes the importance of maintaining functional lightning arresters to ensure protection system efficacy. By optimizing the design and operational parameters of protection equipment, this research contributes to strengthening the resilience of substations, ensuring the safety and reliability of critical infrastructure in areas prone to lightning strikes.